الصلابة النفسية و بعض المتغيرات الديموجرافية كمنبئات معرفية للاتجاهات التطوعية و نوعيتها لدى عينة من طلاب الجامعة - جودة، يسري محمد أبو العنين (جامعة الأزهر - كلية التربية, 2011)
الهدف: هدفت الدراسة الحالية لتحديد دور كل من الصلابة النفسية و بعض المتغيرات الديموجرافية كمنبئات معرفية للاتجاهات التطوعية و نوعيتها لدى عينة من طلاب الجامعة. \\\\ المنهج: تم استخدام المنهج الوصفي الارتباطي حيث تم تصنيف ووصف أداء مجموعات الدراسة على الاختيارات المستخدمة، وتكونت عينة الدراسة الأساسية من (238) من طلاب الجامعة من الجنسين، وقد تم تقسيم العينة وفق مجموعة من المتغيرات وهي الجنس والبيئة لدراسة أثرهما كمتغيرات ديموجرافية بجانب متغيري الصلابة النفسية والمعدل الأكاديمي للطالب على درجة اتجاهه نحو العمل التطوعي ونوعيته. \\\\ النتائج: توصلت نتائج الدراسة إلى وجود ارتباط طردي بين متغير الصلابة النفسية ودرجة الاتجاه نحو العمل التطوعي، ووجود فروق دالة في درجة الاتجاه نحو العمل التطوعي وبعض أنواعه لصالح طلاب الحضر عن طلاب البدو، ووجود فروق دالة لصالح الطالبات في درجة الاتجاه نحو العمل التطوعي ونوعيته، كما وجد تأثير دال لدرجة المعدل الأكاديمي للطالب على درجة اتجاهه نحو العمل التطوعي ونوعيته، وأخيراً وجد تأثير دال لتفاعل درجتي الصلابة لنفسية والمعدل الأكاديمي يسهم في التنبؤ بدرجة الاتجاه نحو العمل التطوعي. Objective: This study aimed to determine the role of each of Psychological Hardiness and some of The demographic Variables as knowledge predicators to Voluntary Attitudes and its quality among a sample of University Students. \\\\ Method: The comparative descriptive approach was used as the performance of study groups were classified and described on the used tests. The sample of the study consisted of (238) of university students of both sexes. The sample has been divided according to a set of different variables that is gender and the environment in order to study their impact as demographic variables besides the variables of psychological hardiness and academic average of the student on its degree on his attitude towards voluntary work and its quality. \\\\ Results: The results of the study showed that there are existence of a link of direct relationship between the variable of psychological hardiness and the degree of attitude towards voluntary work and its quality. There are statistically significant differences in the degree of the attitude towards voluntary work of some types for the benefit of the students in urban students. Also there are statistically significant differences in the degree of the attitude towards voluntary work and its quality for the benefit of girls. There are statistically significant differences of the academic average of the student on his attitude towards voluntary work and its quality. Finally, there are statistically significant differences of the effect of interaction of two classes of psychological hardiness and the academic average helping in predicting of the degree of the attitude toward voluntary work.
775528
Keywords: الجمعيات الخيرية -- الصلابة النفسية -- طلاب الجامعات -- سلوك الطلاب -- التحليل النفسي -- العمل التطوعي -- التنشئة الاجتماعية -- العلاقات الاجتماعية -- التنمية الاجتماعية -- الجامعة و المجتمع